Synthesis of CuInS(2) quantum dots using polyetheramine as solvent - Shei, Shih-Chang (Nanoscale Res Lett, 2015)
This paper presents a facile solvothermal method of synthesizing copper indium sulfide (CuInS(2)) quantum dots (QDs) via a non-coordinated system using polyetheramine as a solvent. The structural and optical properties of the resulting CuInS(2) QDs were investigated using composition analysis, absorption spectroscopy, and emission spectroscopy. We employed molar ratios of I, III, and VI group elements to control the structure of CuInS(2) QDs. An excess of group VI elements facilitated precipitation, whereas an excess of group I elements resulted in CuInS(2) QDs with high photoluminescence quantum yield. The emission wavelength and photoluminescence quantum yield could also be modulated by controlling the composition ratio of Cu and In in the injection stock solution. An increase in the portion of S shifted the emission wavelength of the QDs to a shorter wavelength and increased the photoluminescence quantum yield. Our results demonstrate that the band gap of the CuInS(2) QDs is tunable with size as well as the composition of the reactant. The photoluminescence quantum yield of the CuInS(2) QDs ranged between 0.7% and 8.8% at 250°C. We also determined some important physical parameters such as the band gaps and energy levels of this system, which are crucial for the application of CuInS(2) nanocrystals.